Computational fluid dynamics analysis of hand-cycle aerodynamics with static wheels: Sensitivity analyses and impact of wheel selection - Mannion, P.; Toparlar, Y.; Blocken, B.; Hajdukiewicz, M.; Andrianne, T.; Glifford, E. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Aerodynamics research in cycling has underpinned innovative bicycle design, new refined riding positions and optimised rider apparel. There has been a rise in the level of aerodynamics research focused on cycling since the turn of the millennium, enabled by significant increases in computational power and the availability of software/hardware. However, cycling research has not yet fully embraced para-cycling, with limited studies conducted on the aerodynamic performance of hand-cyclists and other para-cyclists. Wind tunnel experiments and computational fluid dynamics simulations were conducted in this research for the analysis of hand-cycling aerodynamics, focused on competitive H1-H4 category hand-cyclists. A quarter-scale representative geometry of a hand-cyclist was used in high-speed wind tunnel experiments. The accuracy of the simulations performed with the three-dimensional Reynolds-averaged Navier-Stokes equations was found to be dependent on the turbulence model choice and near-wall grid resolution. Computational fluid dynamics simulations predicted the magnitude of the drag and lateral forces to an accuracy of 2.5% using the shear stress transport k-? turbulence model. This study also presents the impact of wheel diameter and disc wheels on hand-cycling aerodynamics via computational fluid dynamics simulations, providing a deeper understanding of the aerodynamic characteristics unique to the hand-cycling discipline in the sport of competitive cycling. Drag reductions of up to 8.9% were found when utilising 20-inch diameter spoked wheels, opposed to the 26-inch wheels. Variations in wheel diameter between the front and rear wheels were found to have a significant impact on the CDA in part through altering the pitch angle of the hand-cycle.